1987
DOI: 10.1152/ajpgi.1987.253.6.g767
|View full text |Cite
|
Sign up to set email alerts
|

GRP-producing nerves control antral somatostatin and gastrin secretion in pigs

Abstract: By immunohistochemistry, nerve fibers containing gastrin-releasing polypeptide (GRP)-like immunoreactivity were identified close to the somatostatin (SS)-producing cells of the gastric antral mucosa. We, therefore, studied the possible role of GRP in the control of antral SS secretion by use of isolated perfused pig antrum with intact vagus nerve supply. Electrical stimulation of the vagus nerves at 4 Hz increased the antral release of GRP up to 10-fold and increased SS output 2- to 3-fold. Atropine at 10(-6) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

1987
1987
2010
2010

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…This is different from the reciprocal relationship that normally exists between gastrin and somatostatin in the antrum (Lundell et al 1988, Wu et al 1991. Similar dual increase of these antral peptides is also seen after stimulation with gastrin-releasing polypeptide and administration of glucocorticoids (Holst et al 1987, Xynos et al 1987, Okazaki et al 1993.…”
Section: Introductionmentioning
confidence: 63%
“…This is different from the reciprocal relationship that normally exists between gastrin and somatostatin in the antrum (Lundell et al 1988, Wu et al 1991. Similar dual increase of these antral peptides is also seen after stimulation with gastrin-releasing polypeptide and administration of glucocorticoids (Holst et al 1987, Xynos et al 1987, Okazaki et al 1993.…”
Section: Introductionmentioning
confidence: 63%
“…The release of gastrin from the G cell is normally stimulated by proteins in the food (Lichtenberger 1982), and inhibited by gastric acidity (Walsh et al 1975). The vagal nerves also stimulate gastrin release via gastrin releasing peptide (GRP) (Holst et al 1987) whereas somatostatin inhibits gastrin release (Bloom et al 1974). We have previously shown that ciprofibrate, contrary to a previous report (Eason et al 1988a), does not inhibit gastric acid secretion (Martinsen et al 1996).…”
Section: Discussionmentioning
confidence: 90%
“…Fresh Fab fragments were prepared (breach experi ment by a modification of a method described by Mage [22] as previously described in detail [23], Before papain digestion, y-globulins of 2 ml of a potent soma tostatin antiserum (code No. 1756) were precipitated with sodium sulfate.…”
Section: Methodsmentioning
confidence: 99%